USULAN DESAIN KEMASAN IKAN ASIN LOME (HARPODON NEHEREUS) MENGGUNAKAN METODE VALUE ENGINERING (StudiKasusPadaUMKM PADAIDI Desa Tanah Merah Kec. Tanah Merah) - Siti Wardah; Mardiana Mardiana (JUTI UNISI, 2017)
Packaging is an important marketing instrument, not just as a wrapper. Packaging is a process associated with the design and manufacture of containers or wrappers for a product. Visual communication design has three basic functions, namely as a means of identification, as a means of information, instruction, and the latter as a means of presentation and promotion. If the business actor takes notice of these functions then the value of the product will increase and the sales of the product can be improved. The purpose of this research is to increase the value of Ikan Asin Lome products by adding function to the proposed packaging design used value engineering method. This research was conducted on UMKM in Tanah Tanah Village ,Tanah MerahSub-district with 22 samples. The results of this study research that used value engineering counting was increased about 17.284% and the results of the differences of old packaging design with new packaging design proposals amounted to 86.81% it can be concluded that there is a significant difference / increase in the value of the new packaging design.